UMP’S mentor minister distributed BB1M - UMP, PNC
It was a joyful moment for 8,531 Universiti Malaysia Pahang (UMP) undergraduates after receiving book vouchers under the ‘Baucar Buku 1Malaysia’ (BB1M) when classes commenced into the second semester of the 2012/2013 session on February 18, 2013.